Altered diurnal states in insomnia reflect peripheral hyperarousal and metabolic desynchrony: a preliminary study. Issue 5 (7th March 2018) - Gehrman, Philip; Sengupta, Arjun; Harders, Elizabeth; Ubeydullah, Er; Pack, Allan I; Weljie, Aalim
Abstract: Study Objectives: Insomnia is a common sleep disorder that is associated with a range of adverse outcomes. Patients with insomnia exhibit hyperarousal in multiple domains, including an elevated metabolic rate, but specific metabolic molecular perturbations are unknown. Furthermore, objective clinical markers of insomnia are not available and current assessment of pathological extent relies on self-report. Here, we provide preliminary evidence that chronic insomnia is remarkably reflected in the periphery through detailed metabolic assessments. Methods: Serum from confirmed patients with insomnia and matched good sleepers ( n = 15 per group) was sampled at high temporal resolution (every 2 hr over 48 hr). Food intake was controlled by providing hourly isocaloric snacks, and sleep architecture was assessed by overnight polysomnography. Quantitative metabolic assessments were conducted using nuclear magnetic resonance spectroscopy. Results: Global metabolic profiles differentiated patients with insomnia from healthy controls, with elevated amino acid and energy metabolites and reduced branched-chain amino acid catabolic products. Strikingly, branched-chain amino acid catabolism was found to be specifically altered during the night with 10 per cent increased accumulation of glucose in insomnia patients. Rhythmicity analysis revealed 11 metabolites that cycled diurnally across both groups, with phase advances noted for acetone and delays for lactate and branched-chain amino acids and their products. Conclusions: These preliminary observations suggest that insomnia is associated with quantitative metabolic dysregulation and supports the hyperarousal hypothesis. Furthermore, we posit that these changes lead to a state of metabolic desynchrony in insomnia that is involved in the pathophysiology of the disorder and/or mediates its impact on health outcomes. Clinical Trials Registration: NCT01957111